Inibição da lipase pancreática e da absorção intestinal de triacilglicerídeos por um extrato de casca de pinhão (Araucaria angustifolia) rico em taninos condensados - Oliveira, Roselene Ferreira de (2015)
Araucaria is a genus of evergreen coniferous trees in the family Araucariaceae. The genus Araucaria includes approximately nineteen species, all confined to the Southern Hemisphere. Two species occur in South America, Araucaria angustifolia and Araucaria araucana. A. angustifolia covers areas of the South and South East of Brazil and North East of Argentine. A. araucana is restricted to high mountain in the South of Argentina and Chile. Their seeds have been consumed from prehistoric times until today cooked in water, baked or as raw flour in regional dishes such as farofa, meat, rice, pancake, soup, gnocchi, mashed, cake, paçoca in Southern Brazil, Argentina and Chile. The aim of the first article work was to review the available literature on the chemical constituents of the seeds, seed coats and leaves of A. angustifolia, in addition to their nutritional and functional properties. This can be justified by the historical and cultural importance of both the A. angustifolia tree and its seeds (pinhão) and its largely unexplored potential for expanding production and marketing. The coat of the cooked or raw pinhão is usually discarded into the environment. It is estimated that approximately 10 tons of pinhão coats are discarded annually. As this coat takes a long time to decompose, several investigations have analyzed possible uses for it. Extracts of A. angustifolia seed coat rich in condensed tannin strongly inhibited both human salivary and porcine pancreatic α-amylase. The purpose of the second article was to characterize the possible inhibition of pancreatic lipase by a tannin rich extract obtained from the pinhão (Araucaria angustifolia seed) coat, based on the previous observation that this preparation inhibits α-amylases. Pinhão seeds used in this study were purchased in a local market (Maringá, PR, Brazil). The seeds used in this work were washed with tap water and dried at room temperature for 24 h. The coats of the seeds were removed and dried at 40 °C until constant weight. After drying, the seed coats were milled in to a fine powder. The powder was mixed with 70% ethanol (in water) at room temperature and maintained under agitation at 140 rpm for 3 h. Alcohol was eliminated using a rotary vacuum evaporator at 40 °C and the remaning solution subsequently was freeze-dried. The porcine pancreatic lipase was assayed using p-nitrophenyl-palmitate as the substrate. One enzyme unit was defined as 1 μmol of p-nitrofenol enzymatically released from the substrate per minute per mL. The intestinal absorption of triglycerides was tested by means of an oral olive oil tolerance test in mice. The mice were deprived of food for 18 h before the experiment. Pinhão coat extract solutions were administered orally with doses of 100, 250 and 500 mg per kg body weight. Olive oil was subsequently administered orally (5 mL per kg body weight). Before and at 1.5, 3.0, 4.5 and 6.0 h after this olive oil administration (or distilled water for the controls) blood samples from the tail vein were analyzed by means of an Accutrend Plus Roche triglycerides meter. Seven groups of mice (n = 3 per group) were utilized: 1) the positive control, only intragastric olive oil (5 mL per kg) administration; 2) the negative control, only tap water administration; 3) intragastric administration of olive oil plus orlistat (50 mg/kg); 4) intragastric administration of olive oil plus A. mearnsii tannin (500 mg/ kg); 5) intragastric administration of olive oil plus 100 mg/kg pinhão extract; 6) intragastric administration of olive oil plus 250 mg/Kg pinhão extract; 7) intragastric administration of olive oil plus 500 mg/Kg pinhão extract. Statistical analysis of the data was done by means of the Statistica program (Statsoft, 1998). Fitting of the rate equations to the experimental initial rates was done by means of an iterative non-linear least-squares procedure using the Scientist software from MicroMath Scientific Software (Salt Lake City, UT). The procedure requires the introduction of preliminary estimates of each parameter. These preliminary estimates are improved by each successive iteration in which the squared difference between the calculated and experimental data is progressively diminished until it converges towards a minimum. The decision about the most adequate model (equation) was based on the model selection criterion (MSC) and on the standard deviations of the optimized parameters. Kinetic measurements of pancreatic lipase revealed that the pinhão coat tannins is an effective inhibitor. The inhibition was of the parabolic non-competitive type. The inhibition constants were equal to 332.7±146.1 and 321.2±93.0 μg/mL, respectively, corresponding roughly to the inhibitor concentration producing 50% inhibition ([I]50). The pinhão extract was also effective in diminishing the plasma triglyceride levels in mice after an olive oil load; 50% diminution of the area under the plasma concentration versus time curve occurred at a dose of 250 mg/kg. The results obtained in the present study revealed that the pinhão coat tannin is an effective inhibitor of pancreatic lipase. Consistently, it was also effective in diminishing the plasma triglyceride levels in mice after a load of olive oil. This is probably the consequence of an indirect inhibition of triglyceride absorption via inhibition of pancreatic lipase. For the pinhão coat tannin this is the second report of biological activity, the first one being a similar inhibition of the absorption of glucose derived from starch in consequence of an inhibitory action on alpha-amylase. All these actions are compatible with a potential anti-obesity action, as suggested for other polyphenol or tannin rich preparations...